Intracellular Membrane Contact Sites in Skeletal Muscle Cells - Matteo Serano; Stefano Perni; Enrico Pierantozzi; Annunziatina Laurino; Vincenzo Sorrentino; Daniela Rossi (Membranes)
Intracellular organelles are common to eukaryotic cells and provide physical support for the assembly of specialized compartments. In skeletal muscle fibers, the largest intracellular organelle is the sarcoplasmic reticulum, a specialized form of the endoplasmic reticulum primarily devoted to Ca2+ storage and release for muscle contraction. Occupying about 10% of the total cell volume, the sarcoplasmic reticulum forms multiple membrane contact sites, some of which are unique to skeletal muscle. These contact sites primarily involve the plasma membrane; among these, specialized membrane contact sites between the transverse tubules and the terminal cisternae of the sarcoplasmic reticulum form triads. Triads are skeletal muscle-specific contact sites where Ca2+ channels and regulatory proteins assemble to form the so-called calcium release complex. Additionally, the sarcoplasmic reticulum contacts mitochondria to enable a more precise regulation of Ca2+ homeostasis and energy metabolism. The sarcoplasmic reticulum and the plasma membrane also undergo dynamic remodeling to allow Ca2+ entry from the extracellular space and replenish the stores. This process involves the formation of dynamic membrane contact sites called Ca2+ Entry Units. This review explores the key processes in biogenesis and assembly of intracellular membrane contact sites as well as the membrane remodeling that occurs in response to muscle fatigue.